An analysis of the use of electronic journals and commercial journal article collections through the FinELib portal - Terttu Kortelainen (Information Research: An International Electronic Journal)
The contents and characteristics of the services of a national electronic library, the FinELIb, were studied in relation to their use. The indicator of the use of the digital library material was the number of printed articles per journal in a year. The sites characterized as e-journals provide developed services utilizing the hypertext structure, 'outlinks', and the possibility of navigating between different materials, and, at least to a certain degree, maintain the structure of a traditional scientific journal. In services characterized as article files, the hypertext structure is utilised less and the unit of information delivered is an article. E-journals are used more heavily, but the article files outnumber them in the number of journals they offer. The services of e-journals and article files complement each other.